Can Evolution Supply What Ecology Demands?. (March 2017) - Kokko, Hanna; Chaturvedi, Anurag; Croll, Daniel; Fischer, Martin C.; Guillaume, Frédéric; Karrenberg, Sophie; Kerr, Ben; Rolshausen, Gregor; Stapley, Jessica
Abstract : A simplistic view of the adaptive process pictures a hillside along which a population can climb: when ecological 'demands' change, evolution 'supplies' the variation needed for the population to climb to a new peak. Evolutionary ecologists point out that this simplistic view can be incomplete because the fitness landscape changes dynamically as the population evolves. Geneticists meanwhile have identified complexities relating to the nature of genetic variation and its architecture, and the importance of epigenetic variation is under debate. In this review, we highlight how complexity in both ecological 'demands' and the evolutionary 'supply' influences organisms' ability to climb fitness landscapes that themselves change dynamically as evolution proceeds, and encourage new synthetic effort across research disciplines towards ecologically realistic studies of adaptation. Trends: Adaptation to a changing environment is far from simple. Ecological demands on populations can vary temporally and spatially. Likewise, the supply of genetic and epigenetic variation is inherently complex. Supply and demands can interact and alter evolutionary trajectories. To track and predict adaptation, we need better integration across disciplines.